THE ANXIETY AND EVALUATION OF 6TH, 7TH AND 8TH GRADE OF ELEMENTARY SCHOOL STUDENTS FOR MATEMATICS - Gülşah GEREZ CANTİMER (Fırat University, 2019)
Anxiety of mathematics is a mental disorder or a nervous strain that students experience in solving mathematical operations and problems. Student’s reaction in this position according to their power of struggle will affect his/her performance and and learning of mathematics because mathematical anxiety contains cognitive and affective elements. If students cope with the anxiety, problems can be overcome, otherwise students don’t have the competence to control this barrier, their performance can decrease. In the literature, due to the fact that anxiety of mathematics is seen an obstacle in student learning, it should be found and tried to be resolved. In this context, the aim in the research is to search the anxiety of mathematics of 6th, 7th and 8th grade students and the evaluations according to their own opinions. The study group that is designed case study, qualitative research methods contain 36 students in 6th grade, 19 students in 7th grade and 17 students in 8th grade including 72 students totally. To examine the anxiety and the evaluation about mathematics lesson of students, a form that has 10 open-ended questions is used and the first four questions were analyzed with the descriptive analysis. According to the findings of the study; when class level increases, it is observed that the level of the mathematics anxiety increases. Especially 7th and 8th grade students have more mathematics anxiety than 6th grade students because of more difficult mathematics concepts. 6th grade students express themselves according to the case of understanding lesson and have positive or negative feelings. 7th grade students have more problems by experiencing in the lesson and so they have anxiety. Also 8th grade students are bored and have some difficulties in the lesson due to the anxiety of exams. Therefore, it may be focused on creating a learning environment that students have positive experience, they can live mathematics in the real life not only be provided a lesson and the opportunities may be provided to overcome from anxiety.